2022
DOI: 10.1002/nop2.1259
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in psychosocial characteristics and diabetes self‐management among inner‐city African Americans

Abstract: Aims To characterize differences in psychosocial variables between inner‐city African American men and women with type 2 diabetes, and to test if the relationships between psychosocial variables and diabetes self‐management behaviours differ by gender. Design Secondary analysis. Methods We used baseline data from participants enrolled in the Prevention through Lifestyle Intervention and Numeracy 4 Success‐Diabetes study ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…Gender plays a fundamental role in the genesis of diabetes and the development of various complications. Meanwhile, (Tseng et al, 2022) research suggests that Men reported better psychosocial features than women except health literacy. According to the literature, women with diabetes tend to seek information about their condition and pay more attention to the symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Gender plays a fundamental role in the genesis of diabetes and the development of various complications. Meanwhile, (Tseng et al, 2022) research suggests that Men reported better psychosocial features than women except health literacy. According to the literature, women with diabetes tend to seek information about their condition and pay more attention to the symptoms.…”
Section: Methodsmentioning
confidence: 99%